PENERAPAN COOPERATIF LEARNING DALAM MENINGKATKAN AKTIVITAS BELAJAR ISLAMIC MULTICULTURAL EDUCATION DI UPTD SD NEGERI TOGUBANG 3 KECAMATAN GEGER - KABUPATEN BANGKALAN - Sholehuddin Sulaiman; Musfirah; Nur Afifah; Mohamad Syaiful Islam; Siti Karimah (Journal Multicultural of Islamic Education, 2023)
This study investigates the application of Cooperative Learning to enhance Islamic Multicultural Education at UPTD SD Negeri Togubang 3, Geger District - Bangkalan Regency, utilizing a qualitative research approach. Cooperative Learning models, including CIRC, Make a Match, IOC, Mind Mapping, Kartu Arisan, and others, were strategically selected based on the Islamic education curriculum. The preparatory phase involved setting objectives, defining tasks, and planning instructional processes. Interviews with educators and observations highlighted the importance of active student participation and group dynamics. Support from the school principal, teacher competency, and student interest were identified as crucial factors facilitating Cooperative Learning success. Challenges, such as limited Islamic Multicultural Education resources, were acknowledged. Despite challenges, Cooperative Learning significantly improved Islamic Multicultural Education activities. The study underscores the need for ongoing support, resource enhancement, and a commitment to pedagogical innovation for sustained effectiveness. The positive impact of student enthusiasm emphasizes the importance of maintaining and encouraging active participation.